2020
DOI: 10.1111/ijcp.13478
|View full text |Cite
|
Sign up to set email alerts
|

Clinical practice guidelines for the management of community‐acquired pneumonia: A critical appraisal using the AGREE II instrument

Abstract: Summary Objective The aim of this study was to appraise the methodological quality of published clinical practice guidelines (CPGs) of community‐acquired pneumonia (CAP) using AGREE II instrument for further enhancing the CAP CPG development. Methods We performed a systematic review of published CPGs on CAP from January 2007 to May 2019. All reviewers independently assessed each CPG using the AGREE II instrument. A standardised score was calculated for each of the six domains. Results Our search strategy ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 61 publications
1
7
0
Order By: Relevance
“…Therefore, this finding could be explained by either improvement in this area with more recent guidelines or more multidisciplinary collaboration across guidelines with pharmacotherapy recommendations. Other studies evaluating CPGs using the AGREE II instrument have generally found highest domain scores in the scope and purpose and clarity of presentation domain, and low scores in the applicability domain much as we have found here 3–9 …”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…Therefore, this finding could be explained by either improvement in this area with more recent guidelines or more multidisciplinary collaboration across guidelines with pharmacotherapy recommendations. Other studies evaluating CPGs using the AGREE II instrument have generally found highest domain scores in the scope and purpose and clarity of presentation domain, and low scores in the applicability domain much as we have found here 3–9 …”
Section: Discussionsupporting
confidence: 78%
“…Previous AGREE II guideline assessments of acute care topics have identified lower scores in items related to stakeholder involvement, applicability and editorial independence, [3][4][5][6][7][8][9] while items related to rigor of development and editorial independence may have the greatest influence on overall perception of guideline quality. 10 A prior study using the AGREE II instrument to evaluate critical care CPGs (published through May 2017) found the lowest AGREE II domain scores exist in stakeholder involvement (Domain 2) and applicability (Domain 5).…”
mentioning
confidence: 88%
See 2 more Smart Citations
“…This is consistent with several previous application of the AGREE II tool to CPGs across various specialties. 15,16,33 Six of the eleven guidelines omitted information about funding sources, and 7 of the eleven guidelines omitted information about potential conflicts of interest.…”
Section: Discussionmentioning
confidence: 99%